2004
DOI: 10.1074/jbc.m314284200
|View full text |Cite
|
Sign up to set email alerts
|

Interference of mRNA Function by Sequence-specific Endoribonuclease PemK

Abstract: In Escherichia coli, programmed cell death is mediated through the system called "addiction module," which consists of a pair of genes encoding a stable toxin and a labile antitoxin. The pemI-pemK system is an addiction module present on plasmid R100. It helps to maintain the plasmid by post-segregational killing in E. coli population. Here we demonstrate that purified PemK, the toxin encoded by the pemI-pemK addiction module, inhibits protein synthesis in an E. coli cell-free system, whereas the addition of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 122 publications
(159 citation statements)
references
References 49 publications
4
149
5
Order By: Relevance
“…8). This result was in striking contrast to all other TA toxins-MazF, PemK, ChpBK, RelE, and HigB-known to target and rapidly degrade mRNA (27,28,30,31). Therefore, we suspected that the presence of Doc might stabilize mRNA.…”
Section: Phd Can Rescue Doc-mediated In Vitro Translation Arrest and contrasting
confidence: 49%
“…8). This result was in striking contrast to all other TA toxins-MazF, PemK, ChpBK, RelE, and HigB-known to target and rapidly degrade mRNA (27,28,30,31). Therefore, we suspected that the presence of Doc might stabilize mRNA.…”
Section: Phd Can Rescue Doc-mediated In Vitro Translation Arrest and contrasting
confidence: 49%
“…Previous results suggested a general mRNA interferase function for ToxN Pa ; however, this activity was not shown directly, and ToxN Pa cleaved housekeeping gene transcripts in vitro even though it was present in complex with its antitoxin (14). In contrast, studies of mRNA interferases from type II TA systems showed that the addition of the antitoxin in a 1:1 stoichiometry completely inhibits the toxin's activity in vitro (16)(17)(18). To confirm the mechanism of ToxN Pa toxicity, Northern blots of the highly expressed housekeeping genes ompA, dksA, and lpp were performed following overexpression of ToxN Pa and the subsequent co-overexpression of ToxI Pa .…”
mentioning
confidence: 84%
“…Another DNA fragment containing a T7 promoter followed by the E. coli era gene was obtained by PCR amplification with the T7 primer 5 0 -AGATCTCGATCCCGCAAATTAAT-3 0 and the primer era-2 5 0 -TTAAAGATCGTCAACGTAACCG-3 0 with pET28a-Era plasmid [12] as template. The Rv0707 mRNA and era mRNA were prepared from these two DNA fragments respectively with the RiboMAX盲 T7 large scale RNA production system (Promega).…”
Section: In Vitro Rna Cleavage By Rv1991cmentioning
confidence: 99%